2020
DOI: 10.7554/elife.56627
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for capsid recruitment and coat formation during HSV-1 nuclear egress

Abstract: During herpesvirus infection, egress of nascent viral capsids from the nucleus is mediated by the viral nuclear egress complex (NEC). NEC deforms the inner nuclear membrane (INM) around the capsid by forming a hexagonal array. However, how the NEC coat interacts with the capsid and how curved coats are generated to enable budding is yet unclear. Here, by structure-guided truncations, confocal microscopy, and cryoelectron tomography, we show that binding of the capsid protein UL25 promotes the formation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 45 publications
2
55
0
Order By: Relevance
“…Accordingly, it has also to be taken into account that the hexagonal core NEC is embedded in a fluid membrane environment, so that the formation of contiguous core NEC coats and the NEC-capsid interaction might be more flexible in distance than initially expected [8]. Very recently, Draganova et al [13] provided additional evidence to show that the HSV-1 NEC coat interacts with capsids and how curved coats may be generated to enable budding. The authors stated that during nuclear budding, binding of pUL25, situated at the pentagonal capsid vertices, promotes formation of core NEC pentagons at the INM.…”
Section: Specific Functional Properties Of Necs and Egress Processes mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it has also to be taken into account that the hexagonal core NEC is embedded in a fluid membrane environment, so that the formation of contiguous core NEC coats and the NEC-capsid interaction might be more flexible in distance than initially expected [8]. Very recently, Draganova et al [13] provided additional evidence to show that the HSV-1 NEC coat interacts with capsids and how curved coats may be generated to enable budding. The authors stated that during nuclear budding, binding of pUL25, situated at the pentagonal capsid vertices, promotes formation of core NEC pentagons at the INM.…”
Section: Specific Functional Properties Of Necs and Egress Processes mentioning
confidence: 99%
“…Site-specific phosphorylation of the nuclear lamins by NEC-associated kinases results in massive rearrangement of the nuclear envelope and particularly the formation of lamina-depleted areas (LDAs), the sites where viral nuclear capsids gain access to the nuclear envelope [10][11][12]. Additional events of nuclear envelope reorganization, including the formation of a hexameric NEC coat and patch-like lattice within the LDAs, apparently serving as a platform for capsid docking, allows the budding of the intranuclear HCMV/herpesviral capsids into the perinuclear space [13]. Hitherto, mainly the regulation of the nuclear egress of individual herpesviruses has been mechanistically investigated and a number of NEC-associated effector proteins have been identified [9,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…We found that an N-terminally truncated UL25 construct UL25∆44 Q72A (Fig. 1 ) inhibited NEC budding at a 10:1 molar ratio of UL25:NEC 20 . Using cryo-ET, we showed that the observed inhibitory effect on the NEC budding correlated with a network of interconnected UL25 stars formed on top of the membrane-bound NEC layer.…”
Section: Introductionmentioning
confidence: 80%
“…Recently, we showed that HSV-1 NEC-mediated budding could be inhibited in vitro by the HSV-1 capsid protein UL25 20 . UL25 is located at the capsid vertices and is thought to anchor the capsid to the NEC during nuclear egress 13 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…5D) may therefore act as a docking platform for copies of pUL25 that would be added in the course of a wild type infection and a-helices contributed by pUL36 at a later stage. This platform, however, is evidently insufficient to retain DNA in the capsid, as the absence of pUL25 alone is enough to completely prevent the emergence of propagation-competent, DNA-filled C-capsids (36), underscoring pUL25's functional versatility as a DNA retention protein and a key player in nuclear egress as well (49).…”
Section: Localization and Interactions Of The Portal In Procapsids Comentioning
confidence: 99%